Spatial Polarization Characteristics of Radar Antenna Analysis, Measurement and Anti-jamming Application - Dai, Huanyao; Wang, Xuesong; Xie, Hong; Xiao, Shunping; Luo, Jia (Springer Nature Singapore : Imprint: Springer, 2019)
This book presents novel research ideas and offers insights into radar system design, artificial intelligence and signal processing applications. Further, it proposes a new concept of antenna spatial polarization characteristics (SPC), suggesting that the antenna polarization is a function of the spatial direction and providing new ideas for radar signal processing (RSP) and anti-jamming. It also discusses the design of an advanced signal-processing algorithm, and proposes new polarimetric and anti-jamming methods using antenna inherent properties. The book helps readers discover the potential of radar information processing and improve its anti-interference and target identification ability. It is of interest to university researchers, radar engineers and graduate students in computer science and electronics who wish to learn the core principles, methods, algorithms, and applications of RSP. .